The perception of employees on performance management system in the Mpumalanga Provincial Department of Culture Sport and Recreation - Maloba, Makgoni Annah (University of Limpopo (Turfloop Campus), 2012)
While performance management is a widely used system in many countries, in South Africa the Public Service Regulations (2001) is a base for a Performance Management and Development System in the public service. The Public Service Regulation (2001) gives effect to performance management systems for purposes of managing performance of individual employees, framework for performance assessment, the outcome and communication of assessment results, and managing unsatisfactory performance, as well as providing a framework on incentives for good performance. Each province is therefore, required to adapt the Performance Management System to its environment to ensure the implementation of the provisions of the Public Service Regulation, (2001). However, as cited by Letsoalo (2010), the introduction of a system of managing performance was received with different reactions, both positive and negative, by the vast majority of employees in the public sector. As a result, this study investigated the attitudes of individual employees towards performance management and development system. The main aim of this research is to present the conclusion drawn from the study, as well as make recommendations emanating from the analysis of information gathered in literature review and through questionnaires completed by departmental staff in the Department of Culture, Sports and Recreation. In identifying different reactions by civil servants to Performance Management and Development System, the study placed an effort in probing different perceptions on Performance Management and Development System amongst employees in the Department of Culture, Sports and Recreation in Mpumalanga Province. There are varying perceptions demonstrated by respondents regarding questions posed to them on the Performance Management and Development System as implemented in the Department of Culture, Sports and Recreation in Mpumalanga Province. There is a perception that the Performance Management and Development System is a penalizing tool used by supervisors on their subordinates and that official’s performance is not duly acknowledged as is supposed to. There is persisting conflict between supervisors and their subordinates resulting from supervisors rating their subordinates without their input, submission of performance results is for compliance It is held in this that the Department of Culture, Sports and Recreation must ensure that effective communication of the system to the rest of the employees of the provincial government is maintained so as to allow employees to understand the system and what is expected of them, the development of the implementation capacity internally through the Performance Management and Development System Champions will in any regard, and as such limit inconsistencies during application of performance management and development system which impacts negatively on the overall performance of the organization.
Thesis (MPA) --University of Limpopo, 2012
Keywords: Performance Management Systems; 658.3125; Performance standards; Performance -- Management